2000
DOI: 10.1002/1521-4141(2000)30:8<2333::aid-immu2333>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MHC class II-presented peptides generated from an antigen targeted to different endocytic compartments

Abstract: We evaluated the capacity of the secretory pathway or of different endocytic compartments in B cell lines to generate MHC class II‐presented peptides from the antigen ovalbumin (OVA). Sorting signals from the transferrin receptor (TFR), targeted a chimeric OVA fusion protein to early endosomes and led to the generation of 8 of 12 presented peptides. Sorting signals from the lysosome‐associated membrane protein 1 (LAMP‐1), targeted an OVA fusion protein to lysosomes, and led to the generation of 9 of 12 peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…[28][29][30] In addition, it was shown that TfR colocalizes with Ii in early endosomes which contain the proteolytic enzymes cathepsin B and D. 31 Thus it is very likely that peptide loading of MHC class II molecules occurs in this compartment. Further support for this conclusion stems from a recent report by Fernandes et al, 32 who demonstrate that in B cell lines TfR-OVA fusion protein is indeed found in early endosomes. Additionally, in this study more OVA peptides were generated and presented on MHC class II from the TfR-OVA fusion than from an OVA version that was targeted to the secretory pathway.…”
Section: Discussionmentioning
confidence: 83%
“…[28][29][30] In addition, it was shown that TfR colocalizes with Ii in early endosomes which contain the proteolytic enzymes cathepsin B and D. 31 Thus it is very likely that peptide loading of MHC class II molecules occurs in this compartment. Further support for this conclusion stems from a recent report by Fernandes et al, 32 who demonstrate that in B cell lines TfR-OVA fusion protein is indeed found in early endosomes. Additionally, in this study more OVA peptides were generated and presented on MHC class II from the TfR-OVA fusion than from an OVA version that was targeted to the secretory pathway.…”
Section: Discussionmentioning
confidence: 83%
“…In this construct, ovalbumin is fused in frame with the transferrin receptor to produce a membrane-bound form of OVA. This protein is transported into the ER and exocytic compartments of cells and then localizes to the plasma membrane and early endosomes (31). In addition, to visualize their intracellular location and for the ease of selection and quantitation by flow cytometry, we also fused these forms of ovalbumin to EGFP.…”
Section: Resultsmentioning
confidence: 99%
“…The PCR product was directly cloned into pCR3.1 plasmid by using TA cloning kit (Invitrogen) and later also subcloned into pcDNA3.1. TfR-OVA was described (31) and subcloned into pcDNA3.1.zeocin. We also generated enhanced GFP (EGFP) fusion constructs with Cyto-OVA, FL-OVA, and TfR-OVA attached to the C terminus of EGFP by PCR.…”
Section: Methodsmentioning
confidence: 96%
“…Several studies have demonstrated that targeting of an Ag to different cellular subcompartments can quantitatively and qualitatively influence the repertoire of CD4 ϩ and CD8 ϩ epitope-specific immune responses elicited by that Ag (5,(22)(23)(24)(25)(26)(27), and it has been postulated that cleavage by the enzymes of a specific cellular compartment can determine the repertoire of epitopes generated by the Ag's processing. Some of these studies have addressed the impact of different targeting mechanisms on a limited number of known CD4 ϩ and CD8 ϩ epitopes; however, the impact of these strategies on the in vivo epitope-specific T cell responses and on the modulation of the whole repertoire of activated cells induced by a protein Ag has not been systematically investigated.…”
Section: T He Establishment Of Mhc-restricted Cd4mentioning
confidence: 99%